2016
DOI: 10.12988/ams.2016.511716
|View full text |Cite
|
Sign up to set email alerts
|

Modelling gold price using ARIMA–TGARCH

Abstract: Statistical models can be used to characterize numerical data so as to understand its behavior and pattern. Gold price model, for example, can give signals to investors as to when they should enter and/or exit the market. To find an appropriate gold price model, it is crucial to choose a model that reflects the pattern of the price movement so as to make the model fit and adequate. This study examines the performances of ARIMA-TGARCH with five innovations in modeling and forecasting gold prices. The innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In recent years, different studies have applied hybrid forecasting models in various fields, and have shown a good performance for rainfall data [ 72 ], for the price of gold [ 73 ], for forecasting daily load patterns of energy [ 74 ], and for stock market prices [ 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, different studies have applied hybrid forecasting models in various fields, and have shown a good performance for rainfall data [ 72 ], for the price of gold [ 73 ], for forecasting daily load patterns of energy [ 74 ], and for stock market prices [ 75 ].…”
Section: Methodsmentioning
confidence: 99%
“…2015.; Yaziz et al. 2016). To capture the possibility of this effect, we model a Threshold Generalised Autoregressive Conditional Heteroskedasticity (TGARCH).…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…The study concluded that traditional symmetric GARCH model was unable to capture the asymmetry volatility response and negative news induced greater volatility, signifying leverage effect. In the same vein, Yaziz et al (2016) examined the performances of ARIMA-TGARCH models of gold price with five innovations in estimation comprising Gaussian, student's-t, skewed student's-t, generalised error distribution and skewed generalised error distribution. Using a total of 2,845 daily gold series data from the years of 2003 to 2014, the study found that a hybrid ARIMA(0, 1, 0) -TGARCH(1, 1) embedded with t-innovation was the best model in forecasting international gold prices.…”
Section: Modelling Gold Volatilitymentioning
confidence: 99%